A climatologia no livro didático : uma análise da coleção didática do livro de geografia do ensino fundamental da Escola Estadual Elmaz Gattas Monteiro – Várzea Grande/MT - Provenzano, Geovaní Rodrigues Pires (2018)
This study presents a discussion about Climatology expressed in elementary school textbooks. The aim of this study is to characterize the meaning of this theme in the context of teaching and learning in order to contribute to the studies on the Teaching of Geography in the scope of Basic Education. Geography addresses the discussions of both physical and social aspects, seeking to articulate the interrelationship between society and nature. In analyzing the process of evolution of geographic thought we find that this has not always occurred satisfactorily, since the traditional geography was mainly based on the description of the earth and the natural elements in a fragmented way and the critical geography brought to this science a new look. Geography as a school discipline based on the traditional slope is based on the memorization and description of the land, while critical geography proposes the analysis of the category space through the dialectic between nature and society. Currently in geography textbooks it is still common to identify a fragmented and dichotomous approach to geographic concepts. Considering that the textbook in the classroom is an extremely usual resource by the teacher, this paper aims to discuss how the concepts of Climatology are approached and presented in the textbooks of Geography of elementary school. In order to understand Brazilian education, it will be presented in this research the main public educational policies and Laws that in recent years contributed to the current structuring and organization of education in the country and that also influenced the definition of the minimum curriculum of Geography proposed by the PCNs, the evaluation, selection and distribution of Geography textbooks in Brazil. The present study was developed in three different moments, the first one being done through a bibliographical review, the second through field research, with data collection from semistructured interviews, and the third and final phase of the study consisted of analysis and interpretation of the data and information obtained during the research. The results of the research allow us to understand that the didactic works of the collection Vontade de Saber - Geografia superficially propose the discussions of climatic concepts and the main types of climate in Brazil, as well as the continents, such discussions being in little depth and of a detached physical character of human and social activities.